PROPERTY CRIME INCIDENCE AND PATTERNS IN MALAYSIA FROM 2007 TO 2017 - Mohd Hakim, Hashom; Lalung, Japareng; Omar Khan, Hussein; Hamzah, Hafezul Helmi; Othman, Mohammad Faiz; Rasudin, Nur Syahmina; Pati, Siddhartha; Nelson, Bryan Raveen; Mat-Ghani, Siti Nor Assyuhada; Chambers, Geoffrey Keith; Edinur, Hisham Atan (PLANNING MALAYSIA, 2022)
Crime is a social problem faced by all communities and ranges from property loss or damage to violent events such as murder and robbery. Crime trends are associated with many factors including mental health, unemployment rates, educational status and policing strategies. In this article, we provide property crime datasets for Malaysia from 2007 to 2017. The data were gathered from all reported cases at district police stations and contingent (state and federal territory levels) headquarters. This information was extracted from the Malaysian Police Reporting System (PRS) and divided into five categories; theft, car theft, motorcycle theft, van/lorry/heavy machinery theft and housebreaking. Overall, there were 1,361,320 property crime cases were reported from 2007 to 2017. Theft and motorcycle theft were observed to be the most common types of property crime in Malaysia. In general, property crime cases continue to decline from 163,317 cases in 2007 to only 77,562 in 2017 due to government initiatives and a proactive policing policy. The same downward trend in overall property crime was also observed at state and federal territory levels and is mainly due to a drop in the volume of theft and motorcycle theft cases.